Molecular Gas in Nearby Galaxies: Star Formation, Molecular Gas and Heating in the Antennae - Schirm, Maximilien R.P. (My University, 2011)
The study of ongoing mergers is vital to understanding how intense star bursts are triggered, and how luminous infrared galaxies and ultra luminous infrared galaxies are formed. The Antennae (NGC 4038/39), at a distance of only 24.9 Mpc, represents the nearest example of a major merger between two gas rich spirals and provides us with a unique laboratory for studying molecular gas and star formation. I have obtained two fully sampled observations of the Antennae using the Herschel SPIRE Fourier Transform Spectrometer which I have supplemented with JCMT CO J = 3 − 2 observations. I detect CO, CI and NII emission throughout both the overlap region and the nucleus of NGC 4038. I measured the integrated intensity of the CO J = 4−3 to 8−7 and find that the overlap region is brighter for all but the J = 4 − 3 line. I find that, in the nucleus of NGC 4038, the CO spectral line energy distribution peaks at the 4−3 transition, while in the overlap region it peaks at the 3−2 transition. I modelled the CO emission using the non-local thermal equilibrium radiative transfer code RADEX coupled with a Bayesian likelihood code. I find a warm (Tkin > 600K) lower density (nH2 ∼ 200cm−3) component of molecular gas in the nucleus of NGC 4038, and similarly in the overlap region (Tkin > 600 K, nH2 ∼ 300cm−3) and find widespread evidence for multiple components of molecular gas throughout the system. These warm components in both regions correspond to ~ 1% of the total molecular gas. I find no evidence of x-ray dominated regions, cosmic rays or turbulent heating being the primary source of heating throughout the galaxy, while photodissociation regions or supernova and stellar winds may be the primary source of heating throughout the galaxy.
Keywords: Submillimeter Astronomy; Molecular Gas; Herschel Space Observatory; Nearby Galaxies; Molecular Gas Heating; External Galaxies; External Galaxies